Hire Purchase Financing: A Case Study of Finance - Gurung, Jas Bahadur (Journal of Nepalese Business Studies, 2007)
This study attempts to analyze the quantitative as well as qualitative information to identify and evaluate the performance and current state of affairs of finance companies in the field of hire purchase financing in Pokhara. The study reveals that the credit-deposit ratios are very satisfactory. The relationship between total deposit collection and total loan to hire purchase loan is highly significant. The businessperson and professional users are predominantly rushing in utilizing the hire purchase financing due to the easy payment terms. The IRR on hire purchase loan is normally higher than their explicit rate of interest and service charge. Except in few cases, there are loan defaulters in all finance companies. In general, the performance of finance companies in hire purchase financing is satisfactory.Journal of Nepalese Business Studies Vol.2(1) 2005 pp.101-109